2009
DOI: 10.1007/s12132-009-9065-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents in the City: Material and Social Living Conditions in Johannesburg–Soweto, South Africa

Abstract: Urban populations are growing rapidly in developing countries. As a result, challenges to the well-being of adolescents are increasing in priority. This paper describes the material and social living conditions of 5,367 young adolescents, in Johannesburg-Soweto, South Africa in [2002][2003]. The majority of children in South Africa's urban hub have adequate access to basic services. However, social conditions are a key concern-lack of financial support by parents; defaulting caregiver roles to grandparents; mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Under the Apartheid regime, people of colour were granted limited access to basic amenities and resources. As a result, multiple generations often resided on the same property or in the same household, sharing resources and caregiving responsibilities (Richter et al, ).…”
Section: A Bioecological Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Under the Apartheid regime, people of colour were granted limited access to basic amenities and resources. As a result, multiple generations often resided on the same property or in the same household, sharing resources and caregiving responsibilities (Richter et al, ).…”
Section: A Bioecological Perspectivementioning
confidence: 99%
“…Coresident grandmothers in South Africa often assume a substantial role in taking care of their grandchildren and in providing the family with emotional, financial and instrumental support (Richter, Panday, Swart, & Norris, ). Research in the United States (U.S.) and Britain has demonstrated that adolescents in two‐generation households benefit from the involvement of their grandparents (Griggs, Tan, Buchanan, Attar‐Schwartz, & Flouri, ; Yorgason, Padilla‐Walker, & Jackson, ), and that adolescents in three‐generation households often fare as well as those living with two parents (DeLeire & Kalil, ).…”
mentioning
confidence: 99%
“…A previous study in the Bt20 cohort revealed that, although housing, water and sanitation conditions have improved, socio-economic inequalities still exist at the household level (Richter et al 2009). The present study strengthens the evidence for socio-economic inequalities within and between the different population groups at the neighborhood level based on adolescents' perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The same year, the Bantu Education Act reinforced inequalities in the education system through the separation of educational facilities between Whites and non-Whites and inferior provision of facilities and resources for Black schools. The Apartheid era led to major differences in the living conditions of these population groups in terms of quality of life, socio-economic status and health (May and Govender 1998;Cameron 2003;Chopra et al 2009;Richter et al 2009). In the post-Apartheid era, some of these distinctions are still apparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation